2022
DOI: 10.1177/23259671221090219
|View full text |Cite
|
Sign up to set email alerts
|

Elongation Patterns of Posterolateral Corner Reconstruction Techniques: Results Using 3-Dimensional Weightbearing Computed Tomography Simulation

Abstract: Background: The isometric characteristics of nonanatomic and anatomic posterolateral corner (PLC) reconstruction techniques under weightbearing conditions remain unclear. Purpose: To (1) simulate graft elongation patterns during knee flexion for 3 different PLC reconstruction techniques (Larson, Arciero, and LaPrade) and (2) compute the most isometric insertion points of the fibular collateral ligament (FCL) graft strands for each technique and report quantitative radiographic landmarks. Study Design: Descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Fourth, we did not assess the elongation pattern of the graft in this study. Previous studies have suggested that studying elongation patterns helps to understand the local strain of the ligament 28,29 . Also, it gives correct advice on the optimal knee flexion angle during the PCL reconstrution 30 .…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, we did not assess the elongation pattern of the graft in this study. Previous studies have suggested that studying elongation patterns helps to understand the local strain of the ligament 28,29 . Also, it gives correct advice on the optimal knee flexion angle during the PCL reconstrution 30 .…”
Section: Limitationsmentioning
confidence: 99%
“…Previous studies have suggested that studying elongation patterns helps to understand the local strain of the ligament. 28 , 29 Also, it gives correct advice on the optimal knee flexion angle during the PCL reconstrution. 30 This study focuses on the effects of different tibial tunnels on graft fixation strength, and it is difficult to evaluate graft elongation patterns based on this biomechanical model.…”
Section: Limitationsmentioning
confidence: 99%